Symposium 1: Interactive and action-oriented instruction for a digital era: A methodological reflection paper - Berg, Jennie (Proceedings of the International Conference on Networked Learning, 2024)
This paper explores and reflects what the methodological considerations are for a study of classroom practice as networked learning. The area of interest is instruction in reading children´s literature in the primary school classroom, i.e., emergent literature didactics. Digitalization processes in society and school involve new conditions for literature didactics and challenges in the classroom. In today`s society we not only communicate in the form of speech and writing, but the digitalization has resulted in that communication takes place through both texts, images, and sound, i. e. multimodal communication (Jewitt, 2008; Godhe et al., 2020). Except for these changed conditions, it is possible to observe decreasing reading frequency, changing attitudes towards reading, and declining reading comprehension among children and youth in Sweden today (Statens Medieråd, 2017; Skolverket, 2017). The overall aim of the PhD thesis is to contribute knowledge about how literature didactics is designed in primary school classrooms, with regards to how this instruction enables encounters with and comprehension of children’s literature, through the support of digital technology. The project consists of three empirical sub-studies with a mixed method approach. In combination with quantitative surveys, qualitative focused observations and interviews with teachers will target instruction in literature didactic, and the role and function of digital technology. Participants are pre- and in-service teachers. The presentation of sub-study I describes how thirty-seven preservice teachers observed classroom teaching during one school day in different primary schools, with the aim to investigate activities related to fiction reading and the role of digital technology in these settings. The study was analyzed by using a thematic content analysis. The preliminary results show that dialogic reading, where the teacher reads fictions texts aloud and orchestrate a dialogue about it with the pupils, is dominating. The activity is supported by document cameras. In the context of this paper, the dialogic reading is understood as part of many pedagogical practices within networked learning, which includes interplays between teacher and pupils or between pupils. The results raise questions about teachers’ motives for literature choices, design, activities, and uses of technology. The analytical tools used in the first study need to be improved, in order to gain a better understanding of the role and function of technology in reading instruction in primary school settings. In addition, complementary empirical data with different foci need to be collected and contrasted with the empirical results from sub-study I.